LEARNING STYLE AND LANGUAGE LEARNING STRATEGIES OF STUDENTS FROM VARIOUS ETHNICS IN INDONESIA - Bonifasius Widharyanto; Heribertus Binawan (Jurnal Cakrawala Pendidikan, 2020)
Learning styles, language learning strategies, and ethnicity are three important factors in language learning. The information about these three things is very useful for language teachers to prepare and implement effective language learning. This study was conducted to describe the students ' learning style and language learning strategy and to know the similarities/differences from the two elements of Java, Papua, Flores, Dayak, and Batak ethnics. A number of 175 participants were involved in the study. Research data were obtained through the Fleming's learning VARK questionnaire and a language learning strategy questionnaire from Oxford. The results of the two questionnaires were analyzed to determine the type of learning style and language learning strategy. The first finding suggests that the main learning styles of students from the five ethnics are variants [aural] and [kinesthetic] including variations in bimodal, and trimodal. The second finding shows that the major language learning strategy is metacognitive and affective. The third finding reveals some similarities and unique differences in their learning style and learning strategy.